Wanprestasi Akibat Keterlambatan Pengantaran oleh Kurir GoFood - Widodo, Slamet Eko; Midia, Fredy Gandhi (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2024)
This article examines the breach of contract issue related to delays in food delivery by GoFood couriers, a rapidly growing food delivery service in Indonesia. Despite the increasing popularity of such services, there is a significant research gap regarding the impact of delivery delays on customer satisfaction. This study aims to analyze the impact of delivery delays on customer satisfaction and identify the factors contributing to these delays. Using a case study analysis method explores specific instances of breach of contract due to delivery delays by GoFood couriers. The results indicate that delivery delays significantly negatively impact customers' perception of GoFood's service. Contributing factors to the delays include traffic conditions, order volume, and company policies. These findings provide valuable insights for GoFood and similar services to enhance delivery efficiency and customer satisfaction. The practical implications of this study include recommendations for improving delivery processes, courier training, and better communication with customers. This research contributes to understanding how delivery delays can affect brand image and customer satisfaction in the context of an evolving food delivery service. In conclusion, the corrective actions taken by the company can help improve service quality and minimize potential conflicts with customers.